PERBEDAAN TINGKAT PEMBELIAN SECARA IMPULSIF BERDASARKAN TINGKAT KECENDERUNGAN, KATEGORI PRODUK, DAN PERTIMBANGAN PEMBELIAN DI SURABAYA - Chrystanti, Elicia Mevita (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Purpose of this study was to determine the differences in the level of impulse purchase based on level trends, product category, and the purchase consideration in Surabaya. This study uses primary data collected through a survey of 100 respondents using questionnaires. In this study the hypothesis was tested by ANOVA analysis technique is a method to examine the relationship between one dependent variable (metric scale) with one or more independent variables (nonmetric scale with more than two categories). Result of this research found that there were differences in impulse buying tendency score significant overall, women have higher tendency than men, there are significant differences in the levels between men and women likely to buy the categories certain products on impulse, and there are significant differences between men and women based on certain considerations that accompany the purchase, that in consideration of the price, the uniqueness of the products, and store atmosphere.